Constitutionalism and Emergency Rule: Comparing Germany’s and Spain’s Responses to the Covid-19 Pandemic. - Rosales, José María (Emerald, 2024)
Regulated differently in modern constitutions, emergency rule is a case of awkward, and dilemmatic, legal fine-tuning of an ambivalent political move that leads the executive of a democratic regime to the verge of the constitutional system. For that reason, as an utmost situation emergency rule becomes a testing field for the resilience of the constitutional order. It affects its own foundations, the basic rights, and thus the constitutional capability to make possible their fulfilment. It also serves to appraise the workings of democratic regimes and, accordingly, the type of legitimacy derived from their institutional performance. And furthermore, it provides a vantage point to watch the reactions of both their representatives and their publics. Focused on the covid-19 pandemic, this paper compares the cases of Germany and Spain through their legal regulations of emergency rule and their governments’ responses. Having rather analogous emergency legislations, from 2020 through 2022 there have been significant differences in their decision-making patterns.
Política de acceso abierto tomada de: https://www.emeraldgrouppublishing.com/publish-with-us/author-policies/our-open-research-policies#green
Keywords: Derecho y COVID-19; Derecho constitucional; Constitutionalism; Emergency rule; Germany’s emergency laws; Spain’s emergency laws; COVID-19 pandemic